Internet Map Server.: Zur Funktionalität und Anwendung eines neuen kartographischen Mediums - Dickmann, Frank (ERDKUNDE, 1999)
Information technology has made it possible to transmit spatial data in the shape of pictures, graphics and maps and allows spatial data and analyses to be got via Internet. The data providers have quickly developed visualizing systems - so-called Internet Map Servers. These systems try to meet the user's multimedia-orientated perception when transmitting spatial data. In contrast to non-digital maps or ordinary HTML-pages respectively Internet Map Servers are characterized by interactive features which make information more individual and specific. In the context of presentation and exploration of spatial data Internet Map Servers offer interesting perspectives in the fields of cartography and geography. The capabilities of these systems are based on an Internet client-server model. The client's basic version of the Web browser is extended, a process which can be carried out through various options. The range of application varies from the downloading of raw data files, which then have to be processed with special software, to map making by users themselves and the performance of GIS retrievals and selections. The variety of file types used in the Internet causes big problems. The realization of an overall standard cannot yet be foreseen. The technical conditions are often closely connected to the potential applications of these visualizing systems, e.g. they depend on whether the aim is to address a wide audience of Internet users or whether the cartographic data should be transmitted for use in a company's intranet application. Today the Internet offers a lot of examples for the application of Internet Map Servers with a majority of servers located at public organizations, e.g. public administration and educational institutions.